Aspects of Authorship, Coauthorship, and Productivity in School Library Research 1998 – 2012 - Brissett, Marilyn M. (Qualitative and Quantitative Methods in Libraries, 2017)
The purpose of this study is to examine authorship and coauthorship characteristics in the approved and published articles in School Library Research, formerly known as School Library Media Research.  The original paper, written to fulfill the requirements to receive the MLIS degree from the University of Southern Mississippi, has been updated to include fifteen (15) volumes spanning fifteen (15) years.  The study was conducted to provide information about the scholarly communication that is taking place in a professional journal whose focus is school librarianship.  It identifies major contributors to school library literature, publication patterns and communication trends that have and are currently taking place, and encourages future research. The findings support studies that report a general trend by scholars to engage in collaborative efforts that appear to increase coauthorship activity and findings support previous studies that found (1) little or no contributions by school librarians in preeminent journals in library and information science literature and (2) library science faculty among the heaviest contributors to library and information science literature. Unlike previous studies, this study indicates that female authors’ contributed and coauthored more articles than their male counterparts.